2020
DOI: 10.1109/access.2020.3017653
|View full text |Cite
|
Sign up to set email alerts
|

Smombie Forecaster: Alerting Smartphone Users About Potential Hazards in Their Surroundings

Abstract: With recent advancements in communication and smartphone technology, many convenient services, such as SNS, gaming, video streaming, and news, are now available to users. However, this wealth of options is disadvantageous in that it makes smartphone users smombies (i.e., users who focus on their smartphones and ignore their surroundings), which poses a safety hazard. For improving the safety of pedestrian smartphone users, attempts have been made to install traffic lights on sidewalks or warn users of approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Delays and potential conflicts in the pedestrian flow can cause inefficient station operation or even safety problems. Inspired by the measure of installing traffic lights on sidewalks by KICT ( 5 ), it may be advisable to deploy clear directions, warning signals, or sounds around bottlenecks to draw passengers’ attention from their smartphones to the surroundings. Thereby, when passengers using smartphones walk by, their attention may be drawn from their smartphones for seconds and they may change their walking patterns (e.g., check point 1, as shown in Figure 14, where those dressed in white are smartphone users, and those in black are normal pedestrians).…”
Section: Results Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Delays and potential conflicts in the pedestrian flow can cause inefficient station operation or even safety problems. Inspired by the measure of installing traffic lights on sidewalks by KICT ( 5 ), it may be advisable to deploy clear directions, warning signals, or sounds around bottlenecks to draw passengers’ attention from their smartphones to the surroundings. Thereby, when passengers using smartphones walk by, their attention may be drawn from their smartphones for seconds and they may change their walking patterns (e.g., check point 1, as shown in Figure 14, where those dressed in white are smartphone users, and those in black are normal pedestrians).…”
Section: Results Of Analysismentioning
confidence: 99%
“…For instance, Korea Institute of Civil Engineering and Building Technology (KICT) attempted to install traffic lights on sidewalks and warn users of approaching vehicles through mobile apps. Seemingly, the duration of pedestrians’ pauses in smartphone usage was increased around 1.59 times by these measures ( 5 ). In Yamato City, Japan, regulations were imposed to prohibit people from using smartphones while walking in public places.…”
mentioning
confidence: 99%
“…In an observational study of pedestrians walking in the street in a medium-sized Spanish city, Fernandez et al (2020) found that certain population groups (especially young women) have a high risk of being involved in accidents due to smartphone usage whilst walking. A related body of research has examined the possibility of introducing smartphoneaided pedestrian safety devices (apps) to alert users of hazards and obstacles whilst walking in public (Goh et al, 2020;Zhuang and Fang, 2020;Kim et al, 2018a;Hincap e-Ramos and Irani, 2014;Foerster et al, 2014;Wang et al, 2012). Indeed, Kashimoto et al (2020) developed such an app to monitor smartphone zombie behaviours over a 15-day period, but their small sample (n 5 7; n 5 5 with complete data) limits the scope of their findings.…”
Section: Previous Research On Smartphone Zombiesmentioning
confidence: 99%
“…(2020) found that certain population groups (especially young women) have a high risk of being involved in accidents due to smartphone usage whilst walking. A related body of research has examined the possibility of introducing smartphone-aided pedestrian safety devices (apps) to alert users of hazards and obstacles whilst walking in public (Goh et al ., 2020; Zhuang and Fang, 2020; Kim et al ., 2018a; Hincapé-Ramos and Irani, 2014; Foerster et al ., 2014; Wang et al ., 2012). Indeed, Kashimoto et al .…”
Section: Previous Research On Smartphone Zombiesmentioning
confidence: 99%
“…Several technologies have been developed to reduce distraction from smartphone use, such as RFID technology [57] or the creation of specific applications for smartphones and tablets [58].…”
Section: Distractorsmentioning
confidence: 99%